ANALISIS SWOT DALAM MENENTUKAN STRATEGI PEMASARAN TERHADAP BISNIS TRAVEL ONLINE ATAU E-COMMERCE MELALUI JEJARING SOCIAL DI ERA PANDEMI COVID-19 - Nur Aeni; Setia Iriyanto (Universitas Muhammadiyah Semarang, 2021)
Since it was founded in Indonesia in 2011. The popularity of Tiket.com as an Online Travel Agent has been the choice of many people to order flight ticketsonline, and has seen an increase from year to year. However, the Covid-19pandemic weakened the national and international economy. Various industrialsectors, including tourism and aviation, experienced disruptions such as flightcancellations. This study aims to determine the strategy that Tiket.com is runningin dealing with airline ticket sales in the era of the Covid-19 pandemic.This research uses descriptive qualitative method. The data collectiontechnique used by researchers is by conducting interviews, observations,questionnaires and then processed using SWOT analysis. Based on the analysis ofthe company's position from the IFAS and EFAS tables, the internal factors are0.87 and the external factors are -0.21. This airline has a position in quadrant II,the diversification strategy was implemented due to the threat situation for thecompany. Based on the SWOT matrix, the strategy that can be taken is the STstrategy. Based on the Internal-External matrix, Tiket.com's position is in box IIwith a total internal strategic value of 2.67 and a total external strategic value of3.23. The growth strategy can be applied with the innovation and marketingstrategies that Tiket.com has been used to penetrate the market.